Levothyroxine for the Treatment of Subclinical Hypothyroidism and Cardiovascular Disease - Sue, Laura Y.; Leung, Angela M. (Frontiers in Endocrinology, 2020)
Subclinical hypothyroidism is a biochemical condition defined by elevated serum thyroid-stimulating hormone levels in the setting of normal levels of the peripheral thyroid hormones, thyroxine and triiodothyronine. Thyroid hormones act on the heart through various mechanisms and subclinical hypothyroidism has been associated with various risk factors for cardiovascular disease, such as hypertension and dyslipidemia. In addition, evidence from multiple studies supports an association between subclinical hypothyroidism and cardiovascular disease. However, the use of levothyroxine in subclinical hypothyroidism to reduce cardiovascular disease risk is not clearly beneficial. Treatment with levothyroxine may only provide benefit in certain subgroups, such as patients who are younger or at higher risk of cardiovascular disease. At present, most of the international societal guidelines advise that treatment decisions should be individualized based on patient age, degree of serum TSH elevation, symptoms, CVD risk, and other co-morbidities. Further study in this area is recommended.